2017
DOI: 10.3390/resources6030030
|View full text |Cite
|
Sign up to set email alerts
|

Households’ Willingness-to-Pay for Fish Product Attributes and Implications for Market Feasibility of Wastewater-Based Aquaculture Businesses in Hanoi, Vietnam

Abstract: A choice experiment was used to assess households' willingness-to-pay (WTP) for informational attributes (sources of water used to rear fish, and certification) of fish products in Hanoi, Vietnam. The study showed that households' purchasing decisions are influenced by their access to information of food product attributes and ascribe an economic value to it. The results indicated that households are willing to pay 51% (USD 1.11 per kg) above the prevailing market price of fish for information to know if waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…In this study, consumers also confirmed their perception that fish consumption is beneficial, expressing moderate (47.8%) to high (37.8%) affirmation of the perceived benefits of consuming fish. This observed consumer perception is similar to other earlier observations reported for the fish-consuming population of Hanoi (Danso et al 2017). Furthermore, the importance of consuming fish has been noted for people who live near Lake Victoria: 98.4% of the interviewed consumers indicated that the inclusion of fish in their diet provided health benefits (Wenaty et al 2018).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, consumers also confirmed their perception that fish consumption is beneficial, expressing moderate (47.8%) to high (37.8%) affirmation of the perceived benefits of consuming fish. This observed consumer perception is similar to other earlier observations reported for the fish-consuming population of Hanoi (Danso et al 2017). Furthermore, the importance of consuming fish has been noted for people who live near Lake Victoria: 98.4% of the interviewed consumers indicated that the inclusion of fish in their diet provided health benefits (Wenaty et al 2018).…”
Section: Discussionsupporting
confidence: 87%
“…This opinion has also been addressed by a previous study (Myrland et al 2000). On the other hand, some studies confirmed that there was no difference in fish consumption based on educational status, and highly educated consumers thought of fish as a "difficultto-prepare" food (Myrland et al 2000;Danso et al 2017). Furthermore, income can influence healthy eating practices and has an impact on fish consumption.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In the study of consumers" willingness to pay for sustainable seafood made in Europe, Zander and Feucht (2018) find a positive attitude of participants toward sustainability in fisheries stating that protection of endangered species, no pollution, and absence of drugs and hormones in production and fishing are the most important issues from the consumer perspective. In the study of households" willingness to pay for fish product in Vietnam, Danso et al (2017) find that households are willing to pay 65% (USD 1.42 per kg) above the prevailing market price for certified fish, which supports the notion of households" concern over the safety of consuming wastewater-raised fish.…”
Section: Econometric Analysis Of Contingent Valuation For the Improvementioning
confidence: 62%